FUNCTIONAL STATE OF RAT KIDNEYS UNDER CONDITIONS OF WATER AND SALT LOADING - Velyka, Alla (European Science, 2024)
The stability of water-salt metabolism is a prerequisite for the normal functioning of the body. After drinking water or in case of its excess in the body, the concentration of soluble osmotically active substances in the blood decreases. It reduces the a